The Role of the Regional Administration of the Tuban Regency Regional Secretariat in Managing Village and Sub- District Boundaries - Brilian Bismart Halska (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The affirmation of village and urban village boundaries is a crucial aspect in ensuring orderly governmental administration and minimizing territorial conflicts. Tuban Regency, with its extensive and complex geographical conditions, requires coordinated and regulation-based boundary management. This study aims to analyze the role of the Regional Administration Division of the Tuban Regency Regional Secretariat in managing village and urban village boundaries. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. Data were analyzed inductively using triangulation techniques to ensure validity. The findings reveal that the Regional Administration plays a strategic role as a facilitator, regulator, and catalyst, as proposed by Gede Diva. As a facilitator, it mediates and coordinates boundary affirmation processes among neighboring villages and urban villages. As a regulator, it applies Minister of Home Affairs Regulation Number 45 of 2016 as the primary legal framework. Meanwhile, its role as a catalyst is reflected through cross-sector collaboration and community involvement, particularly in the implementation of the Gemapatas program. Overall, the Regional Administration significantly contributes to legal certainty, administrative order, and the support of sustainable regional development.